Pengaruh Self Efficacy dan Lingkungan Kerja terhadap Kepuasan Kerja pada Dinas Kependudukan dan Pencatatan Sipil Kota Padang - Aminar Sutra Dewi; Ariska Putri Ananda (Jurnal Manajemen Bisnis Era Digital, 2024)
This research aims to determine the dominant indicators in the variables of Employee Job Satisfaction, Self Efficacy and Work Environment at the Padang City Population and Civil Registration Service and to determine the partial influence of Self Efficacy and Work Environment on employee job satisfaction at the City Population and Civil Registration Service Padang. Research data using primary data was obtained by distributing questionnaires to 46 Padang City DISDUKCAPIL employees. The technique for analyzing the data uses multiple linear regression and t test. The results of Self Efficacy and Work Environment testing influence employee job satisfaction at the Padang City Population and Civil Registration Service. Self Efficacy has a significant effect on employee job satisfaction at the Padang City Population and Civil Registration Service. The work environment has a significant effect on employee job satisfaction at the Padang City Population and Civil Registration Service.This study aims to determine the dominant indicators on the variables of employee performance.